Compound Heterozygous Variants in a Surviving Patient With Alkuraya-Kučinskas Syndrome: A New Case Report and a Review of the Literature - Yue, Ling; Jin, Mei; Wang, Xin; Wang, Jing; Chen, Ling; Jia, Rong; Yang, Zuozhen; Yang, Fan; Li, Jingman; Chen, Cuiying; Zheng, Huacheng; Yang, Huafang (Frontiers in Pediatrics, 2022)
Background: Alkuraya-Kučinskas syndrome is an autosomal recessive disorder characterized by brain abnormalities associated with cerebral parenchymal underdevelopment, arthrogryposis, club foot, and global developmental delay. Most reported cases were cases of premature termination of pregnancies or neonatal deaths. To date, limited studies of nine surviving patients with global developmental delay and intellectual disability have been reported. In this study, we report another surviving patient. Methods: Whole-exome sequencing was utilized for the proband, and variants were filtered, annotated, and classified. Candidate variants were validated by Sanger sequencing of the proband and his family. The literature was reviewed, prognosis among different regions and variant type were analyzed. Results: A nonsynonymous variant (NM_015312.3: exon29: c.4892C>G (p.Pro1631Arg)) was identified and validated in his father. A frameshift duplication (NM_015312.3: exon62: c.10872dupA (p.Arg3625Lysfs*5)) that caused early translation termination was identified in his mother. The literature was reviewed, variants were classified into three regions of KIAA1109, and their survival status was summarized. (add variants results) Conclusion: We reported another survival proband with Alkuraya-Kučinskas syndrome driven by KIAA1109. Our case expands the genotypic spectrum of Alkuraya-Kučinskas syndrome and explored the relationship between the variant region and survival.